THE EFFECTS OF BUDGET PARTICIPATION, ASYMMETRIC INFORMATION, BUDGET EMPHASIS, AND ORGANIZATIONAL COMMITMENT ON BUDGETARY SLACK IN PEMERINTAH KOTA PASURUAN - M. Faruq Dwi Jaya; Toto Rahardjo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research explain the effect of budget participation, asymmetric information, budget emphasis, and organizational commitment on the incidence of budgetary slack in Pemerintah Kota Pasuruan. This research aims to analyze the effect of budget participation, asymmetric information, budget emphasis, and organizational commitment on the incidence of budgetary slack. In this study, sampling was executed with the purposive sampling technique with the number of 125 participants consisting of Satuan Kerja Pemerintah Daerah functionary on Lembaga Teknis Daerah and Dinas Daerah involved in the preparation of the budget on each office in Pemerintah Kota Pasuruan. The data collecting had been done through direct observation and survey which obtained by dividing the questionnaire to the respondent. This study uses multiple regression analysis methods and tested with F-test and t-test. The analysis shows that there are influences of budget participation, asymmetric information, budget emphasis, and organizational commitment on budgetary slack significantly. It shown by the result of statistical analysis with the value of R square is 0,438, it means that the variable of budget participation, asymmetric information, budget emphasis, and organizational commitment influence only 43,8% on budgetary slack. F-test and t-test shows the positive result or proportional, then if budget participation, asymmetric information, budget emphasis and organizational commitment go up, budgetary slack will go up anyway. Keywords : Budget Participation, Asymmetric Information, Budget Emphasis, Organizational Commitment and Slack Anggaran.